GAMBARAN BRAND COMMNICATION BRAND TRUST DAN BRAND LOYALTY PELANGGAN KOSMETIK SARIAYU DI INDONESIA - Pratiwi, Fitri Asti; Utama, Dian H (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to see the description of brand communication, brand trust and brand loyaltyDesign/methodology/approachh - The design of this study was cross sectional method. This research uses descriptive approach with explanatory survey method. The nurses analysis unit is 107 people. Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings - Based on the results of the research using descriptive analysis, the results obtained that brand communication in the quite high category, brand trust in the good category, and brand loyalty in the good category. Originality/value -Â  The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study.